Practical aspects of high resolution esophageal manometry - Antonio Ruiz-de-León-San-Juan (Revista Espanola de Enfermedades Digestivas)
High resolution esophageal manometry (HRM) is currently under development as can be seen in the various Chicago classifications. In order to standardize criteria in certain practical aspects with limited scientific evidence, the First National Meeting for Consensus in High Resolution Manometry of the Spanish Digestive Motility Group took place, bringing together a wide group of experts. The proposals were based on a prior survey composed of 47 questions, an exhaustive review of the available literature and the experience of the participants. Methodological aspects relating to the poorly defined analysis criteria of certain new high resolution parameters were discussed, as well as other issues previously overlooked such as spontaneous activity or secondary waves. Final conclusions were drawn with practical applications.